2022
DOI: 10.3389/fphar.2022.803935
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Metastatic Renal Cell Carcinoma Treatment Patterns and Clinical Outcomes in The Netherlands

Abstract: The number of treatment options for patients with metastatic renal cell carcinoma (mRCC) has significantly grown in the last 15 years. Although randomized controlled trials are fundamental in investigating mRCC treatment efficacy, their external validity can be limited. Therefore, the efficacy of the different treatment options should also be evaluated in clinical practice. We performed a chart review of electronic health records using text mining software to study the current treatment patterns and outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
0
6
1
Order By: Relevance
“…We performed an explorative analysis according to histology which may explain the detrimental effect of non-clear cell histologies for this finding: clear cell a/mRCC patients yielded a PFS of 7.4 months compared to 5.0 months for all other histologies. These 7.4 months (7.7 months for 477 first-line ccRCCs) do not markedly differ from the results of other published real-world data [21][22][23][24]. Only Nikic et al [25] and Schmidinger et al [26] reported relevantly larger PFS of 10.4 and 14 months.…”
Section: Survival Endpointscontrasting
confidence: 41%
“…We performed an explorative analysis according to histology which may explain the detrimental effect of non-clear cell histologies for this finding: clear cell a/mRCC patients yielded a PFS of 7.4 months compared to 5.0 months for all other histologies. These 7.4 months (7.7 months for 477 first-line ccRCCs) do not markedly differ from the results of other published real-world data [21][22][23][24]. Only Nikic et al [25] and Schmidinger et al [26] reported relevantly larger PFS of 10.4 and 14 months.…”
Section: Survival Endpointscontrasting
confidence: 41%
“…Sunitinib has shown a median PFS that was 6 months longer than that of interferon alpha (Motzer et al 2007). A real-world data study in the Netherlands showed a similar median PFS of 15.7 months with pazopanib monotherapy, sunitinib monotherapy, or nivolumab-ipilimumab combination (van Laar et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have examined the prognostic role of clinical and biological characteristics of metastatic renal cell carcinoma [10][11][12][13][14][15] . For example, Xu Y et al showed that a poor performance status in metastatic RCC was significantly associated with inferior overall survival (pooled HR: 2.08, 95% CI: 1.78-2.45) and progression-free survival (pooled HR: 1.51, 95% CI: 1.20-1.91) [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have examined the prognostic role of clinical and biological characteristics of metastatic renal cell carcinoma [10][11][12][13][14][15] . For example, Xu Y et al showed that a poor performance status in metastatic RCC was significantly associated with inferior overall survival (pooled HR: 2.08, 95% CI: 1.78-2.45) and progression-free survival (pooled HR: 1.51, 95% CI: 1.20-1.91) [11] . In addition, a meta-analysis including 19 studies identified performance status as the most decisive independent prognostic factor for survival in a multivariate analysis of 6780 patients with metastatic RCC [13] .…”
Section: Discussionmentioning
confidence: 99%